Epilepsy and electroencephalographic abnormalities in C9orf72 repeat expansion. Issue 1 (2nd January 2017) - Capasso, Margherita; Anzellotti, Francesca; Di Giacomo, Roberta; Onofrj, Marco
Abstract: A patient has been recently described with frontotemporal cognitive decline and C9orf72 repeat expansion who presented abnormally slowed background and photoparoxysmal response at electroencephalographic (EEG) recording. Our data, based on five patients with repeat expansions in C9orf72 and EEG recordings suggest that abnormally slowed background and epilepsy represent previously unrecognized features of the C9orf72 phenotype in some patients.